On Some Geometric Properties of a New Paranormed Sequence Space. (24th April 2014) - Karakaya, Vatan; Altun, Fatma
Abstract : We introduce a new sequence space which is defined by the operatorW = ( w n k ) on the sequence spaceℓ ( p ) . We define a modular functional on this space and investigate structure of this space equipped with Luxemburg norm. Also we study some geometric properties which are called Kadec-Klee, k-NUC, and uniform Opial properties and prove that this new space possesses these properties.